2011
DOI: 10.1037/a0021095
|View full text |Cite
|
Sign up to set email alerts
|

Preschool executive control on the Shape School task: Measurement considerations and utility.

Abstract: Executive functions (EF) necessary for purposeful goal-directed activities undergo rapid change and development during the preschool years. However, of the few psychometrically valid measures of EF suitable for use with preschoolers, information on task sensitivity and predictive validity is scant. The neurodevelopmental correlates of early executive difficulties are also largely unknown. In this study, the discriminant and predictive validity of the recently developed Shape School task (Espy, Bull, Martin, & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
31
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 79 publications
5
31
0
1
Order By: Relevance
“…To begin with, the findings provide initial support for the utility of measures of verbal memory and executive function in predicting which children are at risk for difficulties with academic achievement following early TBI. Therefore, further refinement of these measures for clinical use may prove beneficial in answering need for neurocognitive measures for use with preschool children (Pritchard & Woodward, 2011). Ultimately, the findings may contribute to the development of specific academic interventions designed to mitigate the negative impact of TBI on later academic development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To begin with, the findings provide initial support for the utility of measures of verbal memory and executive function in predicting which children are at risk for difficulties with academic achievement following early TBI. Therefore, further refinement of these measures for clinical use may prove beneficial in answering need for neurocognitive measures for use with preschool children (Pritchard & Woodward, 2011). Ultimately, the findings may contribute to the development of specific academic interventions designed to mitigate the negative impact of TBI on later academic development.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due, in part, to the paucity of developmentally-appropriate neurocognitive measures for young children. However, despite this challenge, recent research with typically developing preschool children has demonstrated that specific neurocognitive skills, such as memory and executive functions, are involved in the development of future academic skills (Bull, Espy, & Wiebe, 2008; Clark, Pritchard, & Woodward, 2010; Espy et al, 2004; McClelland et al, 2007; Pritchard & Woodward, 2011). The identification of specific neurocognitive deficits that contribute to academic difficulties following TBI may have particular importance for children injured during the preschool years, given their heightened vulnerability to negative academic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In concert with these assertions, a growing body of work has emphasized the impact of children's self-regulatory skills on their social competence and academic success (Denham, Brown, & Domitrovich, 2010). For example, self-regulation is found to be related to preschoolers' social competence (Bierman, Nix, Greenberg, Blair, & Domitrovich, 2008;Blair, Granger, & Razza, 2005;Raver et al, 2011), as well as their early math ability and literacy (Altemeier, Abbott, & Berninger, 2008;Bierman et al, 2008;Blair & Razza, 2007;Espy et al, 2004;Ponitz, McClelland, Matthews, & Morrison, 2009;Pritchard & Woodward, 2011;Sesma, Mahone, Levine, Eason, & Cutting, 2009;Welsh, Nix, Blair, Bierman, & Nelson, 2010).…”
mentioning
confidence: 99%
“…For example, EF regulates and modulates other cognitive processes and because these processes may develop at different points and rates throughout childhood, difficulties in assessment arise when development of each facet is not completed. Poor EF performance may reflect only one underdeveloped component rather than EF in its entirety, obscuring estimations of EF abilities for other aspects that are developed or developing (Pritchard & Woodward, 2011;Wiebe et al, 2011).…”
mentioning
confidence: 99%